Penerapan Posisi Semi Fowler terhadap Respiratory Rate pada Pasien Tuberkulosis Paru di RS PKU Muhammadiyah Karanganyar - Arining Setyo; Annisa Andriyani (Pusat Riset dan Inovasi Nasional, 2024)
Background: Tuberculosis is a disease caused by Mycobacterium tuberculosis which attacks the lung organ. one of the symptoms of Pulmonary Tuberculosis is shortness of breath. To stabilize the frequency of breathing in patients with Pulmonary Tuberculosis, one of them is with non-pharmacological therapy, namely the semi-fowler position to help lung development and normalize the frequency of breathing. Objective: To describe the results of the implementation of the semi fowler position on respiratory ratein patients with pulmonary tuberculosis. Methods: Descriptive research design with a case study approach, conducted on two respondents to explore the implementation of the semi fowler position on Respiratory ratein Pulmonary Tuberculosis patients. Results: After the application of the semi fowler position for one day within 30 minutes showed a decrease in respiratory ratein both respondents from the Tachypnea category to the Eupnea category. Conclusion: There is an effect of applying the semi fowler position on the respiratory rateof Pulmonary Tuberculosis patients at PKU Muhammadiyah Karanganyar Hospital.